2022
DOI: 10.1002/adma.202270280
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Silver‐Based Electrochemical Oncolytic Bioreactor (Adv. Mater. 40/2022)

Abstract: Bioreactors In article number 2109973, Liping Zhong, Kun Zhang, Yongxiang Zhao, and co‐workers describe how a tumor‐microenvironment‐enabled in situ silver‐based electrochemical oncolytic bioreactor (SEOB) unlocks antitumor Ag+ prodrugs for highly efficient subcutaneous and orthotopic tumor recession via activating production of reactive oxygen species (ROS). Reduced graphene oxide (rGO), featuring 20‐fold larger catalysis rate than GO, allows intratumoral H2O2 as reductants to reduce Ag+ into silver nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The in situ gelation imparts the system with an ability to continuous release drugs as a drug reservoir, which enables the precise diagnosis or treatment akin to intratumoral nanosynthetic medicine. [ 33–35 ] As expected, in vitro drug release experiments indeed verify that the SAGA@LND composite hydrogels exhibit a better sustained release property than SA and GA (Figure 2k).…”
Section: Resultssupporting
confidence: 73%
“…The in situ gelation imparts the system with an ability to continuous release drugs as a drug reservoir, which enables the precise diagnosis or treatment akin to intratumoral nanosynthetic medicine. [ 33–35 ] As expected, in vitro drug release experiments indeed verify that the SAGA@LND composite hydrogels exhibit a better sustained release property than SA and GA (Figure 2k).…”
Section: Resultssupporting
confidence: 73%
“…To further gauge the ability of these PMPB NCs to eliminate hydroxyl radicals, electron spin resonance (ESR) spectroscopy was conducted by using 5,5‐dimethyl‐1‐pyrroline N ‐oxide (DMPO) as a spin‐trap agent to capture OH radicals produced by the Fenton reaction between Fe 2+ and H 2 O 2 31–33 . Strong ESR signal intensity confirmed that the predicted paramagnetic DMPO/OH adduct stably formed under these reaction conditions, whereas a significant decline in this signal intensity coincided with the increased concentrations of PMPB NCs (Figure 3E), confirming the dose‐dependent elimination of·OH by these NCs.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the highest ROS accumulation by above two actions, the mitochondria of RBE R132C cells in the US+IR780/TPL@Ca‐SA group is violently destroyed, and fails to export Ca 2+ and make Ca 2+ significantly retain in RBE R132C cells, as shown in the strongest red fluorescence signal ( Figure a). Subsequently, the mitochondria membrane potential was tracked, [ 29 ] and JC‐1 monomers represented by green fluorescence signal illuminate all cells in US+IR780/TPL@Ca‐SA (Figure 4b), suggesting the largest drop magnitude of membrane potential and the severest mitochondria damages posed by the highest ROS accumulation. Further, direct mitochondria staining was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…The comprehensive understanding of oncology and the interdisciplinary advances covering medicine, biology, engineering, nanobiotechnology, etc., [ 27–31 ] strengthen our confidence to develop desirable multifaceted nanomodulators to address various limiting factors against ROS production and therapy and cater to the increasing clinical demands. In this report, a multichannel sonocatalysis amplifier has been established via the one‐pot synthesis of triptolide (TPL) and IR780 co‐loaded CaCO 3 nanoparticles modified with DSPE‐mPEG (IR780/TPL@Ca‐SA), which can promote oxidative stress deposition and boost the tumor vulnerability to ROS therapy.…”
Section: Introductionmentioning
confidence: 99%